Analisis Faktor-Faktor yang Mempengaruhi Minat UMKM Terhadap Penggunaan Uang Elektronik Di Kota Padang - Fithri Meuthia, Reno; Putra Ananto, Rangga; Afni, Zalida (Akuntansi dan Manajemen, 2020)
The purpose of the study is to identify the intention to use e-money for SME owners in Padang, West Sumatra. We used the modification of UTAUT model and added Power Distance and Long Time Orientation as new variables. Data were gathered from 128 SME owners who never use e-money in their business activities. Data obtained were analyzed using multiple linear regression analysis for hypotheses testing. The results showed that Social Influence was the most strongly affected behavioral intention to use e-money followed by Performance Expectancy, Power Distance and Effort Expectancy.